2005
DOI: 10.1128/aem.71.11.7285-7291.2005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Carp Interstitial Nephritis and Gill Necrosis Virus in Fish Droppings

Abstract: Carp interstitial nephritis and gill necrosis virus (CNGV) is an unclassified large DNA virus that morphologically resembles members of the Herpesviridae but contains a large (ca. ϳ280-kbp) linear double-stranded DNA. This virus has also been named koi herpesvirus, koi herpes-like virus, and cyprinid herpesvirus 3. CNGV is the cause of a lethal disease that afflicts common carp and koi. By using immunohistochemistry, molecular analysis, and electron microscopy we previously demonstrated that this virus is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 15 publications
2
80
1
1
Order By: Relevance
“…Thus, spring would be the most favorable season for CyHV-3 to multiply in carp tissue and spread throughout the host population. Dishon et al (2005) demonstrated experimentally that infectious CyHV-3 is excreted in the feces by infected hosts. We also detected the CyHV-3 genome in the intestinal contents of common carp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, spring would be the most favorable season for CyHV-3 to multiply in carp tissue and spread throughout the host population. Dishon et al (2005) demonstrated experimentally that infectious CyHV-3 is excreted in the feces by infected hosts. We also detected the CyHV-3 genome in the intestinal contents of common carp.…”
Section: Discussionmentioning
confidence: 99%
“…As fishes are cold blooded, seasonal changes in water temperature are expected to greatly affect CyHV-3 activity in the host. Experiments in aquaria have shown that CyHV-3 is transmitted horizontally from infected to naive hosts through contaminated water (Perelberg et al, 2003;Costes et al, 2009) and that CyHV-3 is discharged from infected hosts through feces (Dishon et al, 2005). A field survey in Lake Biwa revealed that CyHV-3 DNA was detectable in water 5 years after the initial CyHV-3 outbreak (Minamoto et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…PCR primers targeting DNA polymerase gene and the major envelope protein gene of KHV have a sensitivity of 100 femtogram (fg) and 1,000 fg of KHV DNA, respectively in infected gills [41]. KHV can be detected in infected fish dropping by PCR assay with a detection limit of 40 fg of viral DNA [16]. MCP gene has been also used to develop PCR for detection of KHV [68].…”
Section: Molecular Detection Of Viral Dnamentioning
confidence: 99%
“…However, cross-reactivity with related cyprinid herpes virus or non-viral protein is a potential problem with immunostaining. ELISA is also useful in detection of KHV antigen from infected tissues or fish droppings [1,16]. Detection of specific antibodies in serum by ELISA is an indirect method for diagnosis of KHV.…”
Section: Detection Of Khv Antigen/antibodiesmentioning
confidence: 99%
“…Histological examinations show necrotic gills, fusion of lamellae due to hyperplasia of respiration epithelium and even haemorrhagic patches on the tips of lamellae (Hedrick et al 2000;Mohi El-Din 2011). The virus is present mainly in the intestine and kidney, but also in droppings of infected fish (Dishon et al 2005). Moreover, Eide et al (2011) detected KHV DNA in the brain, eye, spleen, gills and in the haematopoietic (anterior) kidney.…”
mentioning
confidence: 98%